(untitled) (Third Sector Social Economic Review, 2018)
Abstract The aim of this study; is to examine the extent of poverty throughout the world and in Turkey, and provide information about the social policies implemented in accordance with the prevention of poverty in Turkey. Growing world economy and increasing global wealth have not shown a positive impact in terms of poverty reduction. In the global world, poverty, which is seen as a consequence of the low level of prosperity of societies and individuals, has been the most problematic of all developed and developing countries. According to World Bank estimates, one billion and four hundred million people in the world are living at an income level of 1.25 a day, and two billion and six hundred million people living at less than 2 a day. The incidence of poverty in Turkey individual, social and economic factors is due to many reasons. We must also ignore the effects of the globalization process on the impoverishment of our country, which is an inevitable problem. The state is fighting poverty through indirect and direct fight programs. Within the scope of direct struggle with poverty, social policies are on the front line and poverty reduction is being tried in this direction.